Gaya Kepemimpinan dan Pelaksanaan Supervisi Kepala Sekolah Untuk Meningkatkan Kinerja Guru - santi santi (Universitas Muhammadiyah Surabaya, 2019)
This study describes the leadership style of principals, describes the teaching supervision program, describes the implementation of teaching supervision, describes the techniques in carrying out supervision of teaching, describes the follow-up by the principal, describes the inhibiting factors of teaching supervision. Descriptive methods with qualitative approaches, carried out in Al-Muhajirin Purwakarta Middle School, observed by the principal, vice-principal and colleagues. The results of the research style of principals' leadership in improving teacher discipline is to use authoritarian and democratic leadership styles. Teaching Supervision techniques used by principals are: Techniques for supervising individuals by doing and group techniques with activities. Follow-up of the results of supervision by the Principal: guidance based on the results of class visits, teacher training programs, opportunities to actively participate in MGMP activities, training both by the local government and the central government or other agencies. Obstacles to supervision: low competence of some appointed supervisors, activities outside the supervision schedule, and difficult to change old habits.